Cost‐effective fabrication of α‐SiAlON ceramics with CeO2 addition for cutting tool applications. Issue 2 (30th October 2022) - Zhang, Jing; Sun, Feng; Zhang, Weiru; Jiang, Changxi
Abstract: SiAlON ceramic tools exhibit unique performance superiority in the machining of nickel‐based heat‐resistant superalloys (HRSA). Production cost is a critical obstacle for the wide application of SiAlON inserts. In this work, the cost‐effective preparation of α‐SiAlON ceramics was implemented using aqueous slurry, and the effects of CeO2 content on the densification, phase composition, microstructure, mechanical properties, and toughening mechanism of the materials were investigated. The addition of CeO2 enhanced the anisotropic growth of α‐SiAlON grains, which enabled the ceramics to obtain higher flexural strength and fracture toughness. Although a decrease in Vickers hardness would occur when CeO2 content was 3 or 5 wt.%, ascribed to the amount increase of the intergranular phase in the samples. The α‐SiAlON ceramics doped with 1‐wt.% CeO2 achieved the extremely high density and mechanical properties with the relative density, flexural strength, Vickers hardness, and fracture toughness of 99.6% ± .1%, 931 ± 62 MPa, 19.7 ± .2 GPa, and 7.2 ± .2 MPa m 1/2, respectively, which could be a candidate cutting tool material for use in the efficient machining of nickel‐based HRSA.